Evaluating the in vitro anti-diabetic activity of Bryonia dioica root extracts supported by molecular docking analysis - Fekhikher Zohra; Benariba Nabila; Radia Brixi Gormat; Hassain Reda; Abdelli Imen; Z. Sekkal Fatima; Kachekouche Youssouf; Taibi Warda; Brikci Sohayb Bekkal; Terki Mohammed; Benramdane Hanane; Adjdir Sara (Digital Chinese Medicine)
Objective: To evaluate the in vitro anti-diabetic effects of Bryonia dioica roots extracts, including water-acetone extracts and their ethyl acetate and butanol fractions, and chloroform-methanol extracts. Methods: The total phenolic, flavonoid, flavonol, and saponin contents in the Bryonia dioica root extracts (chloroform-methanol extracts, water-acetone extracts and their ethyl acetate and butanol fractions) were determined using colorimetric methods with Folin-Ciocalteu, aluminum trichloride, and vanillin reagents, respectively. The in vitro anti-diabetic activity was evaluated by measuring the half-maximal inhibitory concentration (IC50) values of these root extracts against α-amylase and α-glucosidase activities, evaluating their effects on α-amylase kinetics, quantifying the inhibition of bovine serum albumin (BSA) glycation using fluorometry to assess advanced glycation end products (AGE) production, and determining glucose uptake by isolated rat hemidiaphragm. Additionally, molecular docking analysis was conducted to investigate the binding affinity and interaction types between Bryonia dioica ligands (cucurbitacin B, bryogénin, vitexin, and isovitexin) and target enzymes, and a phytochemical-targets interaction network was constructed. Results: For α-amylase inhibition, ethyl acetate fraction demonstrated the most potent activity (IC50 = 145.95 μg/mL), followed by chloroform-methanol extract (IC50 = 300.86 μg/mL). Water-acetone root extracts and their ethyl acetate and butanol fractions inhibited the α-glucosidase activity with IC50 values ranging from 562.88 to 583.90 μg/mL. Both ethyl acetate and butanol fractions strongly inhibited non-enzymatic BSA glycation (IC50 = 318.26 and 323.12 μg/mL, respectively). The incubation of isolated rat hemidiaphragms with the ethyl acetate fraction (5 mg/mL) significantly increased glucose uptake (35.16%; P < 0.0001), exceeding the effects of insulin (29.27%), chloroform-methanol extract (24.07%), and catechin (15.27%). Molecular docking revealed that cucurbitacin B exhibited the strongest docking scores against α-amylase (– 16.4 kcal/mol), and α-glucosidase (– 14.2 kcal/mol). Compared with other ligands, isovitexin formed the maximum number of hydrogen bonds with the α-amylase active site residues (Asp300, Asp197, and Glu233), α-glucosidase residues (Ser13, Arg44, Met86, Gly10, Asp39, and Tyr131) and other residues (Arg195, Trp59, His299, and Tyr62). Network analysis identified 36 overlapping targets between Bryonia dioica phytochemicals and type 2 diabetes mellitus-associated genes, with cucurbitacins and polyphenols interacting with α-amylase, α-glucosidase, and Glut4 translocation pathway targets. Conclusion: Bryonia dioica root extracts demonstrated promising in vitro anti-diabetic activity through multiple mechanisms, including the inhibitory effect on digestive enzymes, protein antiglycation potential, and enhancement of glucose uptake, suggesting their potential as a source for anti-diabetic drugs development.